Consensus statement for the management of dyslipidemia and hypertension in the Indian population with diabetes - P. B., Jayagopal; Rao, M. Srinivas; Vijaykumar, R.; Kumar, Soumitra; Parthan, Girish (International Journal of Advances in Medicine, 2019)
The mortality rate from cardiovascular disease (CVD) in India is higher than the global figures (272 per 100,000 persons vs. 235 per 100,000 persons, respectively). Smoking, obesity, hypertension, diabetes and dyslipidemia are the known risk factors for atherosclerotic cardiovascular disease (ASCVD). The treatment of either condition aims to reduce the risk of ASCVD. This goal is achievable only when a holistic, simultaneous treatment is initiated and is monitored to reduce the blood glucose, blood cholesterol, and BP. India heralds a huge population of nearly 73 million people with diabetes. Diabetes is one of the major contributors of ASCVD, dyslipidemia and hypertension often coexist with diabetes. Patients diagnosed with either condition need risk stratification, followed by defining the treatment target for each risk category and developing appropriate treatment strategies based on the risk category. Unfortunately, there is no clear guideline that defines the treatment targets and subsequent management. This statement has been created based on the vast experience and an extensive literature review conducted by experts from multidisciplinary teams to address several treatment dilemmas that are routinely faced by clinicians when treating their patients with diabetes. An attempt is made to provide well-defined answers to these quandaries. This statement discusses screening, diagnosis, risk stratification, treatment targets, and management of dyslipidemia and/or hypertension in patients with diabetes and provides a roadmap for the treatment of Indian patients to curtail the risk of ASCVD.